Global, regional, and national burden of multiple sclerosis from 1990 to 2019: Findings of global burden of disease study 2019 - Qian, Zhen; Li, Yuancun; Guan, Zhiqiang; Guo, Pi; Zheng, Ke; Du, Yali; Yin, Shengjie; Chen, Binyao; Wang, Hongxi; Jiang, Jiao; Qiu, Kunliang; Zhang, Mingzhi (Frontiers in Public Health, 2023)
Background: The global rising prevalence and incidence of multiple sclerosis (MS) has been reported during the past decades. However, details regarding the evolution of MS burden has not been fully studied. This study aimed to investigate the global, regional, and national burden and temporal trends in MS incidence, deaths, and disability-adjusted life years (DALYs) from 1990 to 2019 by using the age-period-cohort analysis. Methods: We performed a secondary comprehensive analysis of incidence, deaths, and DALYs of MS by calculating estimated annual percentage change 1990 to 2019 obtained from the Global Burden of Disease (GBD) Study 2019. The independent age, period, and birth cohort effects were evaluated by an age-period-cohort model. Results: In 2019, there were 59345 incident MS cases and 22439 MS deaths worldwide. The global number of incidence, deaths, and DALYs of MS followed an upward trend whereas the ASR slightly declined from 1990 to 2019. High socio-demographic index (SDI) regions had the highest ASR of incidence, deaths, and DALYs in 2019, while the rates of death and DALYs in medium SDI regions are the lowest. Six regions which include High-income North America, western Europe, Australasia, central Europe, and eastern Europe had higher ASR of incidence, death, and DALYs than other regions in 2019. The age effect showed that the relative risks (RRs) of incidence and DALYs reached the peak at age 30-39 and 50-59, respectively. The period effect showed that the RRs of deaths and DALYs increased with the period. The cohort effect showed that the later cohort has lower RRs of deaths and DALYs than the early cohort. Conclusions: The global cases of incidence, deaths, and DALYs of MS have all increased, whereas ASR has declined, with different trends in different regions. High SDI regions such as European countries have a substantial burden of MS. There are significant age effects for incidence, deaths, and DALYs of MS globally, and period effects and cohort effects for deaths and DALYs.